A 2-year follow-up of a randomized multicenter study comparing a paclitaxel drug-eluting balloon with a paclitaxel-eluting stent in small coronary vessels the BELLO study. (1st April 2015) - Naganuma, Toru; Latib, Azeem; Sgueglia, Gregory A.; Menozzi, Alberto; Castriota, Fausto; Micari, Antonio; Cremonesi, Alberto; De Felice, Francesco; Marchese, Alfredo; Tespili, Maurizio; Presbitero, Patrizia; Panoulas, Vasileios F.; et al.
Abstract: Background/objectives: A prospective, multi-center, randomized trial, BELLO (Balloon Elution and Late Loss Optimization), showed that the primary endpoint of in-stent (in-balloon) late loss was significantly less with drug-eluting balloons (DEB) as compared with paclitaxel-eluting stents (PES). At 6 months, DEB and PES were associated with similar rates of angiographic restenosis, target lesion revascularization (TLR), and major adverse cardiac events (MACE) defined as death, myocardial infarction and target vessel revascularization. The aim of this study was to report 2-year clinical outcomes after treatment of de novo small vessel disease with DEB as compared with PES. Methods: A total of 182 patients were enrolled and randomized to treatment with DEB (n = 90) in 94 lesions or PES (n = 92) in 98 lesions. The study endpoint was the incidence of MACE at 2-year follow-up. Results: Two-year follow-up was achieved in almost all cases (97.8% in DEB group vs. 98.9% in PES group). There was a trend towards a lower incidence of MACE in the DEB group as compared with the PES group (14.8% vs. 25.3%; p = 0.08). TLR rates in the DEB group were acceptable at 6 months, 1 year and 2 years and did not differ significantly from the PES group (4.4% vs. 7.6%, p = 0.37; 6.7% vs. 12.1%, p = 0.23; 6.8% vs. 12.1%, p = 0.25, respectively). Conclusions: Our results suggest that treatment of small vessel disease with a paclitaxel DEB is associated with a trend for improved clinical outcomes as compared with PES up to 2 years. Late catch-up phenomenon requiring repeat intervention after treatment with DEB was not evident in this study. Highlights: This is the first study to report long-term follow-up outcomes following treatment of small coronary artery disease with DEB. DEB use in this lesion subset was associated with a trend towards lower MACE rates at 2 years as compared to PES. Late catch-up phenomenon requiring repeat intervention was not evident after treatment with DEB.